2004
DOI: 10.1001/jama.291.16.1972
|View full text |Cite
|
Sign up to set email alerts
|

HER-2 Testing in Breast Cancer Using Parallel Tissue-Based Methods

Abstract: HE HUMAN EPIDERMAL GROWTH factor receptor 2, HER-2 (HER-2/neu or c-erbB-2), oncoprotein is overexpressed in 20% to 25% of invasive breast cancers. 1 Previous studies have supported the importance of HER-2 overexpression as an independent prognostic marker of clinical outcome, 1-5 as a predictor of benefit from doxorubicin-based chemotherapy, 6,7 and for metastatic disease, for benefit from the anti-HER-2 antibody, trastuzumab. 8-11 Determination of HER-2 status is now an integral part of the clinical-pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
280
3
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(310 citation statements)
references
References 34 publications
24
280
3
3
Order By: Relevance
“…32,33 Although fluorescence in situ hybridization is globally accepted as a standard method for determining EGFR status, pathologists have been reluctant to adopt fluorescence in situ hybridization for routine clinical laboratory testing. The reasons for this include the technical challenges associated with fluorescence in situ hybridization assays, 34 the expenses, the required time for interpretation 35 and the relative lack of community-based experience with this technology. Although the material costs are slightly higher for silver enhanced in situ hybridization than for fluorescence in situ hybridization (approximately costs per each test for silver enhanced in situ hybridization: 200$, for fluorescence in situ hybridization: 130$), the technician working time for silver enhanced in situ hybridization is much shorter compared with fluorescence in situ hybridization (pure working time for silver enhanced in situ: 20 min, for fluorescence in situ hybridization 3 h).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Although fluorescence in situ hybridization is globally accepted as a standard method for determining EGFR status, pathologists have been reluctant to adopt fluorescence in situ hybridization for routine clinical laboratory testing. The reasons for this include the technical challenges associated with fluorescence in situ hybridization assays, 34 the expenses, the required time for interpretation 35 and the relative lack of community-based experience with this technology. Although the material costs are slightly higher for silver enhanced in situ hybridization than for fluorescence in situ hybridization (approximately costs per each test for silver enhanced in situ hybridization: 200$, for fluorescence in situ hybridization: 130$), the technician working time for silver enhanced in situ hybridization is much shorter compared with fluorescence in situ hybridization (pure working time for silver enhanced in situ: 20 min, for fluorescence in situ hybridization 3 h).…”
Section: Discussionmentioning
confidence: 99%
“…Four tumors showed alterations in two components of the PI3K pathway. 1 Tumor RELB_090 could not be screened for PIK3CA mutations due to insufficient DNA.…”
Section: Pten Loss Of Function Can Be Accurately Identified By Ihc Anmentioning
confidence: 99%
“…Human epidermal growth factor receptor 2 (HER2) overexpression is observed in 15% of breast cancers. 1,2 Activating mutations in PIK3CA, which encodes the PI3K catalytic subunit, have been reported in approximately a quarter of breast tumors 3 and copy number gain of this gene has been identified in 1-14% of breast cancers. [4][5][6] Approximately one fifth of breast cancers are described as having loss of phosphatase and tensin homologue deleted on chromosome 10 (PTEN) expression (range 4-48%) [6][7][8][9][10][11][12][13][14][15] and epigenetic silencing of the PTEN gene through promoter hypermethylation has been reported in 34% 16 and 48% 17 of breast cancers.…”
mentioning
confidence: 99%
“…However, these first approximations possibly over stated the true frequency of HER2+ expression in the general breast cancer population [11]. Indeed, Yaziji et al observed 18.6% HER2+ expression in a large volume quality control program [12]. Bilous et al reported 12% HER2+ expression in the HER2000 International Study [13].…”
Section: Frequency Distribution For Her2 (±) And/or Er (±) Expressionmentioning
confidence: 99%